Effects of annealing on microstructures and electrochemical properties of La0.8Mg0.2Ni2.4Mn0.10Co0.55Al0.10 alloy - 宋大卫 王一菁 刘毅 韩树民 焦丽芳 袁华堂 (Journal of rare earths, 2008)
The La0.8Mg0.2Ni2.4Mn0.10Co0.55Al0.10 alloy was prepared by induction melting. The structural and morphological characterizations were performed by means of X-ray powder diffraction （XRD） and scanning electron microscopy （SEM）. The electrochemical measurements were performed using LAND and CH/660b electrochemical workstation. The main phases of the alloy were LaNi5 and （La,Mg）Ni3. After annealing, the maximum discharge capacity, cycle stability and high rate dischargeability （HRD） were improved obviously. The maximum discharge capacity reached 373.80 mAh/g （T=1173 K）, the C100/Cmax（%） was 72.63% （T=1173 K）, and the value of HRD reached 51.8% at a discharge current density of 1150 mA/g （T=1173 K）. The cyclic voltammetry （CV） and potentiodynamic polarization were also studied.